Demonstration of differences in colonic volumes, transit, chyme consistency and response to psyllium between healthy and constipated subjects using magnetic resonance imaging - Major, Giles; Murray, Kathryn; Singh, Gulzar; Nowak, Adam; Hoad, Caroline L.; Marciani, Luca; Silos-Santiago, ada; Kurtz, Caroline B.; Johnston, Jeffrey; Gowland, Penny; Spiller, Robin C. (Wiley, 2018)
Background: In functional gastrointestinal disorders a lack of objective biomarkers limits evaluation of underlying mechanisms. We aimed to demonstrate the utility of Magnetic Resonance Imaging (MRI) for this task using psyllium, an effective constipation treatment, in patients and controls.